Atom-probe tomography characterization of the oxidation of stainless steel - Lozano-Perez, S; Saxey, D; Yamada, T; Terachi, T (2010)
Three-dimensional atomic characterization of oxidation in stainless steels under simulated nuclear reactor conditions has been achieved with atom-probe tomography (APT). By combining high spatial resolution and high chemical sensitivity, the ingress of oxygen and other trace elements has been studied on an "atom-by-atom" basis, together with their interaction with microstructural defects. APT has revealed how the highly dislocated microstructure in cold-worked stainless steels accelerates the oxidation and the formation of oxide precursors beyond the oxide-metal interface. © 2010 Acta Materialia Inc.